Causal pathways of the productive impacts of cash transfers: Experimental evidence from Lesotho. (March 2019) - Prifti, Ervin; Daidone, Silvio; Davis, Benjamin
Highlights: Cash transfers increase farm production by 33.5 percent. None of these impacts are channelled through transfer-induced changes in farm labour. In fact, cash transfers have no significant impact on family labour supply or on demand for hired labour. This implies that the productive impacts of cash transfers flow through other channels, different from the labour one. Abstract: This paper has the double aim to study whether unconditional cash transfers have an impact on farm production and to look into the causal mechanisms through which government transfers produce productive impacts. We use mediation analysis to identify the total effect of transfers on farm production and to isolate the influence of the labour channel from other transmission channels. In particular, we analyze whether changes in farm production are caused by transfer-induced changes in the use of farm labour – either by reallocating family labour between off- and on-farm work or by changes in the demand for hired labour – or if other transmission channels are at work. We find that cash transfers have a sizable impact on farm production but they do not lead to increased use of family or hired labour on the farm, which implies that the productive impacts of cash transfers flow through other channels, different from the labour one.